A New Biphenyl from the Fruits of Schisandra lancifolia and Its Cytotoxicity - Wang, Huan; Liu, Gui-You; Yang, Juan-Xia; Lou, Jie; Li, Limei; Hu, Qiu-Fen; Ye, Yan-Qing; Gao, Xue-Mei (Asian Journal of Chemistry, 2015)
A new biphenyl i.e., lancibiphenyl A (1) was isolated from the fruits of Schisandra lancifolia. The structure of 1 was elucidated by spectroscopic methods including extensive 1D- and 2D-NMR techniques. Compound 1 was evaluated for its cytotoxicity and it exhibited moderate cytotoxicity against A549 and PC3 cell with IC50 values of 6.4 and 5.7 μM, respectively.